Evidence of the Enemy Release Hypothesis: Parasites of the Lionfish Complex (Pterios volitans and P. miles) in the Western North Atlantic, Gulf of Mexico, and Caribbean Sea - Simmons, Kayelyn Regina (NSUWorks, 2014)
Invasive species are becoming more common as human interactions within coastal waters and the aquarium trade continues to increase. The establishment of the invasive lionfish complex Pterois volitans and P. miles from the Indo-Pacific to the Western Atlantic, Gulf of Mexico, and the Caribbean Sea has had significant negative effects on reef fish biodiversity and economically important species. Their rapid colonization and success has been attributed to their biological and ecological life history traits as well as their absence of predation. Past research has highlighted these characteristics; however, there is a knowledge gap in lionfish parasitism. This research explored the enemy release hypothesis as a key success factor in rapid establishment in the invaded range on a biogeographical scale. The diversity of lionfish parasitism was compared among 15 geographically diverse sites within the invaded range, incorporating the time of introduction at each site. Eight new parasites are described for the first time in the invasive lionfish: (1) a Cymothoid isopod: Rocinela stignata, (2) four nematodes: Raphidascais sp., Contraceacum sp., Paracuria adunca and Hysterothylaceum sp., (3) one digenean: Tergestia sp., (4) two acanthacephalans: Serracentis sp. and Dollfusentis sp., and (5) two cestodes: Nybelinia sp. and Tentacularia sp. Lionfish from the east coast of Florida exhibited the highest abundance in parasite fauna while other invaded areas yielded low abundance and diversity. Comparisons between lionfish parasitism from the past native range studies and the invaded range suggest that vectors of time, life history traits, and trophic interactions structure the lionfish parasite community. Lionfish in the Western Atlantic and Caribbean were found to be host for generalists parasite species within the coastal ecosystem. Consequently, lionfish have relatively low parasite abundance, supporting the enemy release hypothesis and its direct relation to their invasion success.